Comparative government and politics : an introduction - Hague, Rod.; Harrop, Martin (Basingstoke : Palgrave Macmillan, 2013)
Long established as the leading text in the field, the new edition has been comprehensively updated and rewritten. Accessible, student-friendly and truly international in its coverage, this edition includes an brand new chapter on voters and increased coverage of rising powers, such as India and Brazil
1. Political Concepts 2. The State 3. Democracy 4. Authoritarian Rule 5. Theoretical Approaches 6. Political Culture 7. Political Communication 8. Political Participation 9. Interest Groups 10. Political Parties 11. Elections 12. Voters 13. Constitutions and Law 14. Multilevel Governance 15. Legislatures 16. The Political Executive 17. Bureaucracy and Public Management 18. The Policy Process 19. Comparative Methods
Previous edition: 2010.
economic&political bookfair2015
Includes index.
Keywords: Comparative government